2020
DOI: 10.1155/2020/4693750
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Framework for Revealing Competitive Travel Times with Low-Carbon Modes Based on Smartphone Data Collection

Abstract: Evaluating potential of shifting to low-carbon transport modes requires considering limited travel-time budget of travelers. Despite previous studies focusing on time-relevant modal shift, there is a lack of integrated and transferable computational frameworks, which would use emerging smartphone-based high-resolution longitudinal travel datasets. This research explains and illustrates a computational framework for this purpose. The proposed framework compares observed trips with computed alternative trips and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…The present paper extends the framework proposed by Bagheri et al [55], using longitudinal data collection of revealed travel behavior of individuals for exploring the potential for shifting to low-carbon travel alternatives in a target urban region. In comparison to previous development, this current, extended, computational framework analyzes changes in travel time together with emission reductions and physically active travel, by considering variable time-increase thresholds.…”
Section: Computational Frameworkmentioning
confidence: 82%
See 4 more Smart Citations
“…The present paper extends the framework proposed by Bagheri et al [55], using longitudinal data collection of revealed travel behavior of individuals for exploring the potential for shifting to low-carbon travel alternatives in a target urban region. In comparison to previous development, this current, extended, computational framework analyzes changes in travel time together with emission reductions and physically active travel, by considering variable time-increase thresholds.…”
Section: Computational Frameworkmentioning
confidence: 82%
“…In addition, the filtering process discards non-stop circular trips, such as running exercises, where such trips start and end at the same geolocation. Additional details on data collection and filtering have been discussed in Bagheri et al [55] and Rinne et al [45]. Further details about accuracy and noise in the data collection, informed by the findings of the case study, are also discussed in the discussion section of this paper.…”
Section: Data Collection and Filtering Of Trip Ddatamentioning
confidence: 99%
See 3 more Smart Citations